Digitalisasi Grey Literature sebagai Strategi Pengembangan Koleksi pada Perpustakaan Fakultas Hukum Universitas Sriwijaya - Novita Vitriana; Triady Hermansyah (Pustabiblia: Journal of Library and Information Science, 2021)
One type of library collection that must be digitized is the gray literature collection, namely the literature typical of the institution, both published and unpublished. The purpose of this study was to determine the implementation and process of digitization in the Unsri Library and also the processing of gray literature. The method used is descriptive qualitative research method with a comparative approach and data collection techniques are carried out through observation, interviews and literature study. The results of this study indicate that the process of media transfer for Gray Literature manuscripts in the Sriwijaya University Library is the identification and checking (validation) of collections in the database; separation of collections that will be transferred and those that will not (including list generation); media transfer and file processing; upload process to system; and destruction of print collections when they are no longer needed by making a report.